Effective Implementation of Assimilation and Integration Programs for Correctional Inmates (WBP) in Reducing Prison Overcapacity - Hakim Siregar, Dzikril; Rafianti, Fitri; Zarzani, T. Riza (International Conference Epicentrum of Economic Global Framework, 2026)
Overcapacity in correctional institutions (lapas) and state detention centers (rutan) in Indonesia constitutes a structural problem that has not been fully resolved. This condition has serious implications for the quality of correctional rehabilitation for inmates (WBP), the fulfillment of prisoners’ human rights, and security stability within correctional facilities. This study aims to analyze the implementation of assimilation and integration programs for WBP based on their mechanisms, stages, and applicable statutory provisions, as well as to evaluate their effectiveness in reducing overcapacity in correctional facilities and detention centers. The research employed a normative juridical method using a statute approach and a conceptual approach, supplemented by field research at the Class III Langkat Youth Correctional Institution. Data were collected through library research, observation, and interviews with correctional officers and WBP. The findings indicate that the assimilation and integration programs regulated under Law Number 22 of 2022 on Corrections and Ministerial Regulation Number 7 of 2022 have been implemented through a staged mechanism encompassing inmate data registration, deliberation by the Correctional Observer Team (TPP), and supervision by the Community Correctional Center (Bapas). The programs have proven capable of significantly reducing prison occupancy rates and facilitating the social reintegration of WBP. However, their implementation continues to face challenges, including limited supervisory human resources, social stigma, and weak inter-agency coordination. This study concludes that the assimilation and integration programs constitute a strategic and constitutional solution for addressing prison overcapacity, provided they are implemented selectively, measurably, and sustainably.